Effectiveness of Oral Stimuly Cold Therapy (Popsicle) on Thirst Perception in Postoperative Patients: A Systematic Review - Wati Melawati; Debie Dahlia; Sri Yona; Liya Arista (GLOBAL HEALTH SCIENCE GROUP, 2025)
Thirst after surgery is commonly experienced by patients, with prevalence reaching 70-80% within the first 24 hours postoperatively. This condition, often overlooked in clinical practice, can impact the quality of patient recovery. Popsicle, as a form of oral stimuli cold therapy, offers an effective solution to alleviate this complaint. Objective: This study aims to evaluate the effectiveness of popsicle therapy in reducing thirst and improving comfort and the quality of recovery in postoperative patients.Methodology: A systematic review approach was used by analyzing five scholarly articles based on randomized controlled trials (RCT) and quasi-experimental designs from 2018–2024. The keyword search used was popsicle OR